2022
DOI: 10.5194/acp-22-13389-2022
|View full text |Cite
|
Sign up to set email alerts
|

Examination of brown carbon absorption from wildfires in the western US during the WE-CAN study

Abstract: Abstract. Light absorbing organic carbon, or brown carbon (BrC), can be a significant contributor to the visible light absorption budget. However, the sources of BrC and the contributions of BrC to light absorption are not well understood. Biomass burning is thought to be a major source of BrC. Therefore, as part of the WE-CAN (Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption and Nitrogen) study, BrC absorption data were collected on board the National Science Foundation/National Center for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…75 Numerous previous studies have observed correlations between levoglucosan and BrC from biomass combustion. [76][77][78] A growing number of studies show that levoglucosan may not be stable in the atmosphere for long periods of time [79][80][81] which further suggests that we sampled BB plumes that had undergone minimal atmospheric processing. The quan-tied terpene concentrations were comparable to the sugar concentrations and were likely formed from heat-induced volatilization of unburnt biomass in the wildres.…”
Section: Association Between Brc Light Absorptivity and Chemical Comp...mentioning
confidence: 99%
“…75 Numerous previous studies have observed correlations between levoglucosan and BrC from biomass combustion. [76][77][78] A growing number of studies show that levoglucosan may not be stable in the atmosphere for long periods of time [79][80][81] which further suggests that we sampled BB plumes that had undergone minimal atmospheric processing. The quan-tied terpene concentrations were comparable to the sugar concentrations and were likely formed from heat-induced volatilization of unburnt biomass in the wildres.…”
Section: Association Between Brc Light Absorptivity and Chemical Comp...mentioning
confidence: 99%
“…The liquid sample from the PILS was sent to a Brechtel Fraction Collector to collect samples for offline analysis (Sorooshian et al., 2006). The PILS liquid flowrates were set and the fraction collector operated similarly to the approach used during WE‐CAN (Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen) to obtain ∼1.2 mL of liquid sample every 2 min (Sullivan et al., 2022). Pre‐loaded carousels were manually switched during flight.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, higher RH decreased the MAC of secondary BrC derived from α-pinene, suggesting that the effect of RH on MAC may differ depending on the type of VOCs. It is noted that a rise in RH may result in increased liquid water content in wildfire aerosols, where water-soluble organics can contribute to a large portion (e.g., ∼45% at 405 nm) of BrC light absorption . Despite the extensive investigations, the effect of RH on secondary BrC formation remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%